MAKNA DERIVASIONAL DAN INFLEKSIONAL VERBA NASAL BAHASA JAWA DIALEK AREK - Wicaksono, Nur Hanifa; Nurhayani, Ika; Khasanah, Ismatul (Universitas Hamzanwadi, 2022)
This study aims to observe the change in the meaning of the nasal verbs in the Arek dialect of Javanese. The scope of the research is limited to the speeches of the community verbs in the Arek zone in Malang Regency. The research data was done from 7-17 April 2022 in 3 districts: Sumberpucung, Kalipare, and Kromengan. The data of this study were analyzed according to Bauer's theory of derivational and inflectional meanings. The results showed that the Javanese nasal verbs have more derivation processes than inflections. The derivation process marks the derivational meaning and the inflection process marks the inflectional process. The results of the study revealed that almost all nasal allomorphs which act as nasal affixes make a verb derivation. The researcher divided the nasal allomorph into 2 parts, /m/, /ñ/, and/ŋ/ which have 2 roles of affixes which is derivational and inflectional. Second, the nasal allomorphs /ŋǝ/, /n/, and /ṇ/ have 1 affix role. Both classifications apply the terms and conditions of the initial phoneme of a verb.Key words : Derivasional, Inflectional, Verb, Nasal, Javanese.